What Drives Authorization in Mobile Applications? A Perspective of Privacy Boundary Management - Jie Tang; Bin Zhang; Umair Akram (Information, 2021)
Personal information has been likened to “golden data”, which companies have chased using every means possible. Via mobile apps, the incidents of compulsory authorization and excessive data collection have evoked privacy concerns and strong repercussions among app users. This manuscript proposes a privacy boundary management model, which elaborates how such users can demarcate and regulate their privacy boundaries. The survey data came from 453 users who authorized certain operations through mobile apps. The partial least squares (PLS) analysis method was used to validate the instrument and the proposed model. Results indicate that information relevance and transparency play a significant role in shaping app users’ control–risk perceptions, while government regulation is more effective than industry self-discipline in promoting the formation of privacy boundaries. Unsurprisingly, privacy risk control perceptions significantly affect users’ privacy concerns and trust beliefs, which are two vital factors that ultimately influence their willingness to authorize. The implications of conducting a thorough inquiry into app users’ willingness to authorize their privacy information are far-reaching. In relation to this, app vendors should probe into the privacy-relevant beliefs of their users and enact effective privacy practices to intercept the economic and reputational damages induced by improper information collection. More significantly, a comprehensive understanding of users’ willingness to authorize their information can serve as an essential reference for relevant regulatory bodies to formulate reasonable privacy protection policies in the future.